To find the new equation of the line after translating it one unit to the right and two units up, we can start with the original equation \(y = 3x + 2\).
-
Shifting the line one unit to the right involves replacing \(x\) with \(x - 1\): \[ y = 3(x - 1) + 2 \] Simplifying that: \[ y = 3x - 3 + 2 = 3x - 1 \]
-
Shifting the line two units up involves adding 2 to the entire equation: \[ y = (3x - 1) + 2 \] Simplifying that: \[ y = 3x + 1 \]
So, the equation of the new line after the translation is: \[ y = 3x + 1 \]
Therefore, the correct response is: y = 3x + 1.